Analytical Modeling Approach of Routing Deflection for Intra-domain Networks - Gomes, Rodolfo R.; Dominicini, Cristina K.; Liberato, Alextian B.; Ribeiro, Moisés R. N.; Martinello, Magnos (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2016)
This paper presents an analytical modeling to KAR (Key-for-Any-Route), an intra-domain resilient routing system in which edge-nodes set a route ID to select any existing route as an alternative to safely forward packets to their destination. KAR-enabled switches explore the existing routes by using special properties of Residue Number System as encoding and forwarding techniques. The encoding technique allows adding resilient forwarding paths to drive deflected packets (due to link failure) to their original destination so that loops are not formed. Three deflection methods are discussed along with their analytical models checked against numerical simulations. Results show that KAR efficiently allows deflected packets to automatically reach their destination.